Exploring Adolescent Pregnancy Expectations in Continuity of Midwifery Care: A Qualitative Study in Indonesia - Susanti, Dewi; Hardisman, Hardisman; Yusrawati, Yusrawati; Mudjiran, Mudjiran; Machmud, Rizanda; Nursal, Dien Gusta Anggraini; Maputra, Yantri; Hasnita, Evi (Poltekkes Kemenkes Palu, 2023)
Introduction: Adolescent pregnancy presents a significant challenge to global reproductive health, including in Indonesia. The unique obstacles that young pregnant women encounter when seeking appropriate and supportive healthcare services call for a deeper understanding to improve maternal care. Purpose: This study aims to explore the expectations of young pregnant women regarding continuous midwifery care in Indonesia. Method: This research employed an exploratory qualitative approach, conducting 13 face-to-face interviews between January and June 2022. Participants included midwives, young mothers, a coordinating midwife, and Mother and Child Health (MCH) program holders. Interviews, lasting 1-1.5 hours, were conducted, and the interview data were rigorously analyzed thematically by the research team, strengthening data reliability through triangulation. Results: Continuity management emphasizes friendly service, privacy, clear communication, and comprehensive health assessments. Informational continuity involves comprehensive information, direct communication, attractive aids, and health education evaluation. Relational continuity highlights comprehensive maternal care, family tradition approval, reminders, and efficient care. The study underscores the importance of tailored, holistic, and culturally sensitive midwifery care for young pregnant women's overall well-being. Conclusion: This study highlights adolescent pregnant women's unique needs, focusing on continuity management, informational continuity, and relational continuity. Proposed strategies include tailored health services, comprehensive maternal education, cultural sensitivity training for healthcare providers, policy integration, and diverse research. Successfully implementing these measures can significantly enhance maternal care outcomes for Indonesian adolescents.